2020
DOI: 10.14814/phy2.14622
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular responses to graded exercise in young healthy males and females

Abstract: Although systemic sex‐specific differences in cardiovascular responses to exercise are well established, the comparison of sex‐specific cerebrovascular responses to exercise has gone under‐investigated especially, during high intensity exercise. Therefore, our purpose was to compare cerebrovascular responses in males and females throughout a graded exercise test (GXT). Twenty‐six participants (13 Females and 13 Males, 24 ± 4 yrs.) completed a GXT on a recumbent cycle ergometer consisting of 3‐min stages. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Additionally, recent studies have shown no difference in the CBF response to moderate-intensity exercise between females and males 106,107 with sex-related differences in CBF regulation only apparent at severe intensity exercise (80–100% maximal workload). 108 As such, we do not expect that the inclusion of 5 female participants in the fixed intensity submaximal exercise protocol (0, 50, 75, 100 watts) would affect the variability of our results. Future investigations are merited to address any sex-related differences in cerebrovascular acid-base regulation in response to respiratory and exercise-induced metabolic acidosis.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, recent studies have shown no difference in the CBF response to moderate-intensity exercise between females and males 106,107 with sex-related differences in CBF regulation only apparent at severe intensity exercise (80–100% maximal workload). 108 As such, we do not expect that the inclusion of 5 female participants in the fixed intensity submaximal exercise protocol (0, 50, 75, 100 watts) would affect the variability of our results. Future investigations are merited to address any sex-related differences in cerebrovascular acid-base regulation in response to respiratory and exercise-induced metabolic acidosis.…”
Section: Discussionmentioning
confidence: 76%
“…Of the 1,174 participants collectively included in this systematic review, 727 (61.9 %) identified as male, 379 as female (32.29 %), whereas the sex of 68 (5.79 %) was not reported. Sex may impact the CBF response to exercise; for example, Ashley and colleagues (2020) found that the cerebral vascular conductance index (CVCi) was significantly greater in females compared to males in their sample, while the cerebral perfusion pressure (CPP) was significantly greater in males compared to females.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies using parameters of internal load to determine exercise intensity (Andrianopoulos et al, 2018;Billaut et al, 2010;Billinger et al, 2017;Billinger et al, 2021;Burma et al, 2020;Ellis et al, 2017;Faulkner et al, 2016;Fisher et al, 2013;Furlong et al, 2020;Giles et al, 2014;Hiura et al, 2009;Hiura et al, 2013;Hiura et al, 2018;Ichinose et al, 2020;Klein et al, 2019;Labrecque et al, 2020;Lyngeraa et al, 2013;Malik et al, 2018;Monroe et al, 2016;Parfitt et al, 2017;Perdomo et al, 2019;Pontifex et al, 2018;Rattray et al, 2017;Robertson et al, 2015;Santos-Concejero et al, 2017;Sato et al, 2011;Shibuya et al, 2004;Steventon et al, 2019;Steventon et al, 2020;Tsubaki et al, 2018;Tsubaki et al, 2016;Witte et al, 2019) focused on Vo2max, heart rate reserve (HRR), peak work rate (WRpeak), peak oxygen uptake (VOpeak), and perceived exertion rates (Borg, 1970). On the other hand, experiments using parameters of external load centered around Watt (W) as a measure of exercise intensity (Ashley et al, 2020;Billinger et al, 2017;Braz et al, 2017;Fisher et al, 2013;Fisher ...…”
Section: Exercise Characteristicsmentioning
confidence: 99%
“…The cardiovascular response to exercise differs between men and women, even when similar relative intensities were used (Ogawa et al ., 1992). Thus, CBF and CSF flow dynamics during exercise may also differ by sex, as suggested by studies using transcranial Doppler (TCD) (Ward et al ., 2018; Joshi & Edgell, 2019; Ashley et al ., 2020). Therefore, the purpose of the present study was to characterize CBF and CSF flow dynamics during moderate‐intensity RHG exercise using cine PC‐MRI in young healthy men and women.…”
Section: Introductionmentioning
confidence: 99%